Boshlang'ich Sinf O'quvchilarida Pirls Xalqaro Baholash Nazoratiga Tayyorlash Metodikasi - Ahmadaliyeva Gulhayo Asqarali qizi (Open Academia, 2024)
Progress in International Reading Literacy Study (PIRLS) is a popular assessment of fourth graders ' reading comprehension skills internationally. Since primary education serves as the basis for the academic level of the student, preparing them for PIRLS assessment is essential for developing strong literacy skills and academic excellence. This article examines the comprehensive methodology of preparation for the PIRLS International Assessment and emphasizes important components that help elementary students excel in Reading Literacy
Keywords: PIRLS; baxolash; educational programs; primary class